Growth performance and reproductive efficiency of weaned NZW rabbits as affected by HCG injection - El Gaafary M.N.; El Kelawy H.M.E.; Marai I.F.M.; Yamani K.A.O.; Abd-Allah F.R.; Amin R.S. (Rabbit production in hot climates, 1994)
Twenty-four females and eighteen males of 1.5 up to 4 months of age were used to study the effects on injection of 50 IU human chorionic gonadotrophin (HCG; Pregnyl) on growth performance, gonadal weight, hormonal activity and histological structure of the reproductive organs of growing male and female New Zealand White (NZW) rabbits during pre-sexual maturity. Semen characteristics of the bucks and doe post-maturity traits were also studied. Following HCG injection, live body weight, weight gain and testes weight increased significantly (P less than 0.01 or 0.05) and ovaries weight was not affected in the pre-pubertal rabbits. The concentration of testosterone in the males and progesterone in the females increased significantly (P less than 0.01) by HCG injection. The histopathological studies showed that the tests were more developed and consisted of mature seminiferous tubules with mature spermatocytes in the injected males. The number of mature follicles in the female ovaries increased more in the injected than in the control does. Mild degeneration of hepatic cells in both injected males and females were noticed, while kidneys were normal in their structure. Semen quality was improved following injection of the bucks with HCG. Considerable improvement was also observed in the doe traits when mating was carried out between injected males and injected females. The parity showed no significant effect on most of the doe traits.
1. International Conference of rabbit production in hot climates, 1994/09/06-08, Cairo (Egypt)